Pendekatan Metode Prophet dalam Peramalan Nilai Ekspor Jawa Tengah untuk Perencanaan Ekonomi Daerah - Rio Wahyu Saputra; Mujiati Dwi Kartikasari (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2026)
Export plays an important role in promoting regional economic growth. Central Java Province, as one of the regions with significant international trade activities, contributes to the national export value. However, the export value of Central Java has shown fluctuations influenced by various factors, such as global economic dynamics, the COVID-19 pandemic, and trade policies. Therefore, a forecasting method capable of producing accurate predictions is needed to support regional economic planning and policy decision-making. This study aims to forecast the export value of Central Java for the period 2019–2025 using the Prophet method based on monthly data obtained from the Central Java Provincial Statistics Agency (BPS). The dataset was divided into 70% training data and 30% testing data. The modelling process utilized the trend, seasonality, and holiday components available in the Prophet method. Model performance was evaluated using the Root Mean Square Error (RMSE) and Mean Absolute Percentage Error (MAPE) accuracy measures. The results show that the best-performing model yields an RMSE of 54.094 and an average MAPE of 16.2317%, indicating a good level of forecasting accuracy. The forecasting results also indicate that the export value of Central Java is expected to increase until the end of 2025, with the highest export value predicted to occur in December at approximately 1,028.44 million US dollars.